Evaluation by Flow Cytometry of Mature Monocyte Subpopulations for the Diagnosis and Follow-Up of Chronic Myelomonocytic Leukemia - Picot, Tiphanie; Aanei, Carmen Mariana; Flandrin Gresta, Pascale; Noyel, Pauline; Tondeur, Sylvie; Tavernier Tardy, Emmanuelle; Guyotat, Denis; Campos Catafal, Lydia (Frontiers in Oncology, 2018)
Chronic myelomonocytic leukemia (CMML) is a myelodysplastic/myeloproliferative neoplasm, characterised by persistent monocytosis and dysplasia in at least one myeloid cell lineage. This persistent monocytosis should be distinguished from the reactive monocytosis which is sometimes observed in a context of infections or solid tumors. In 2015, Selimoglu-Buet et al. observed an increased percentage of classical monocytes (CD14+/CD16- >94%) in the peripheral blood of CMML patients. In the present study, using multiparametric flow cytometry (MFC), we assessed the monocytic distribution in peripheral blood samples and in bone marrow aspirates from 63 patients with monocytosis or CMML suspicion, and in 7 follow-up blood samples from CMML patients treated with hypomethylating agents. A control group of 12 healthy age-matched donors was evaluated in parallel in order to validate the analysis template. The CMML diagnosis was established in 15 cases in correlation with other clinical manifestations and biological tests. The MFC test for the evaluation of the repartition of monocyte subsets, as previously described by Selimoglu-Buet et al., showed a specificity of 97% in blood and 100% in marrow samples. Additional information regarding the expression of intermediate MO2 monocytes percentage improved the specificity to 100% in blood samples allowing the screening of abnormal monocytosis. The indicative thresholds of CMML monocytosis were different in PB compared to BM samples (classical monocytes >95% for PB and >93% for BM). A decrease of monocyte levels in PB and BM, along with a normalization of monocytes distribution, was observed after treatment in 4/7 CMML patients with favorable evolution. No significant changes were observed in 3/7 patients who did not respond to hypomethylating agents therapy and also presented unfavorable molecular prognostic factors at diagnosis (ASXL1, TET2, IDH2 mutations). Considering its simplicity and robustness, the monocyte subsets evaluation by MFC provides relevant information for CMML diagnosis.